Disruption of peroxisome function leads to metabolic stress, mTOR inhibition, and lethality in liver cancer cells. (1st May 2018) - Cai, Mengjiao; Sun, Xiao; Wang, Wenchao; Lian, Zhusheng; Wu, Ping; Han, Suxia; Chen, Huan; Zhang, Pumin
Abstract: Peroxisome houses a large number of enzymes involved in lipid and phytochemical oxidation as well as synthesis of bile acid and other specialized lipids. Peroxisome resident enzymes are imported into the organelle via a conserved cargo transport system composed of many peroxins, protein factors essential for the biogenesis of peroxisome. Among the peroxins, PEX5 plays a transporter role, and PEX2, 10, and 12 are thought to form a complex that functions as an E3 ubiquitin ligase to help recycle PEX5 in an ubiquitin modification-dependent process. Previous studies have demonstrated the importance of peroxins in postnatal development especially the development of nerve systems. These studies also show that peroxins or the function of peroxisomes is dispensable for cellular viability. In contrast, however, we report here that PEX2 and other peroxins are essential for the viability of liver cancer cells, probably through altering metabolism and signaling pathways. Our results suggest that peroxins may be potential targets of therapeutics against liver cancer. Graphical abstract: Highlights: Peroxisome function is essential in liver cancer cells. Normal peroxisome function maintains the activity of mTORC1. Autophagy in liver cancer cells is induced by dysfunctional peroxisomes.